2018
DOI: 10.1002/phar.2107
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Medication Adherence and the Outcomes of Heart Failure

Abstract: Incremental medication adherence was associated with reductions in emergency department visits, hospital admissions, length of hospital stay, and all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
42
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 31 publications
9
42
1
Order By: Relevance
“…In the present study we have identified the non-adherence in 20 of 81 (25%) CHF patients. Compared to previous studies (5,6,8,9), the frequency of non-adherence was relatively low and the adherence to individual drug classes including diuretics and beta-blockers was relatively high in our study. We can only speculate about reasons.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…In the present study we have identified the non-adherence in 20 of 81 (25%) CHF patients. Compared to previous studies (5,6,8,9), the frequency of non-adherence was relatively low and the adherence to individual drug classes including diuretics and beta-blockers was relatively high in our study. We can only speculate about reasons.…”
Section: Discussioncontrasting
confidence: 93%
“…Non-adherence to prescribed medication has been reported in 11-60% CHF patients (3-10) as well as its negative effect on acute decompensations and mortality rate (3,5,6,(8)(9)(10). Finally, the negative economic impact of non-adherence to CHF medication has been also proven (23,24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of drugs in patients with coronary heart disease and heart failure is lifelong and continuous usage is needed. Results of some researches prove that the continuous usage of drugs in coronary heart disease and heart failure patients show signs of positive impact in clinical outcome of the patients and medical cost controlling 8,9 . Full-covered medical cost is one of the factors that give contribution to continuous usage of drugs in heart and blood vessel disorders 10 .…”
Section: Direct Medical Cost Analysis Among Coronary Heart Disease Anmentioning
confidence: 99%
“…It's frequency is anticipated to increase in the future, especially in ageing populations (1) . Patients with HF are commonly prescribed multiple medications for which they have low treatment adherence, resulting in poor health outcomes (2) . Pharmacological agents such as beta blockers (BB), angiotensin converting enzyme inhibitors (ACEI)/angiotensin receptor blockers (ARB) and mineralocorticoid receptor antagonists (MRA) have proven to play an effective role in reducing the mortality related with HF.…”
Section: Introductionmentioning
confidence: 99%